Acculturation of Islamic Law and Betawi Customs in Historical Perspective - Biem Benjamin; Richard Richard (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This study examines the process of acculturation between Islamic law and customary law in Betawi society from a historical perspective. Using qualitative research methods with secondary data analysis, this article traces the historical traces of the entry of Islam into Batavia/Betawi and its interaction with pre-existing local traditions. The analysis focuses on key domains such as family law (marriage and inheritance), life cycle rituals, and mechanisms of community governance and dispute resolution. It is found that acculturation is not a linear process, but rather a complex dynamic involving harmonization, syncretism, adaptation, negotiation, and sometimes conflict, especially evident in inheritance law practices. External factors such as Dutch colonial legal policies (e.g., theorie receptie) and the development of post-independence Indonesian national law (Marriage Law No. 1/1974, Compilation of Islamic Law) have also shaped the landscape of interaction between these two normative systems. This study concludes that Betawi society, with a strong Islamic identity, dynamically negotiates and integrates Islamic teachings with their customary heritage, resulting in unique and ever-evolving socio-legal practices.